Multiple T Cell Subsets Control Francisella tularensis LVS Intracellular Growth Without Stimulation Through Macrophage Interferon γ Receptors - Cowley, Siobhán C. (The Rockefeller University Press, 2003)
A variety of data suggest that in vivo production of interferon (IFN)-γ is necessary, but not sufficient, for expression of secondary protective immunity against intracellular pathogens. To discover specific IFN-γ–independent T cell mediated mechanisms, we took advantage of an in vitro culture system that models in vivo immune responses to the intracellular bacterium Francisella tularensis live vaccine strain (LVS). LVS-immune lymphocytes specifically controlled 99% of the growth of LVS in wild-type murine bone marrow–derived macrophages. Surprisingly, LVS-immune lymphocytes also inhibited LVS intracellular growth by as much as 95% in macrophages derived from IFN-γ receptor knockout (IFNγR KO) mice. CD8(+) T cells, and to a lesser degree CD4(+) T cells, controlled LVS intracellular growth in both wild-type and IFNγR KO macrophages. Further, a unique population of Thy1(+)αβ(+)CD4(−)CD8(−) cells that was previously suggested to operate during secondary immunity to LVS in vivo strongly controlled LVS intracellular growth in vitro. A large proportion of the inhibition of LVS intracellular growth in IFNγR KO macrophages by all three T cell subsets could be attributed to tumor necrosis factor (TNF) α. Thus, T cell mechanisms exist that control LVS intracellular growth without acting through the IFN-γ receptor; such control is due in large part to TNF-α, and is partially mediated by a unique double negative T cell subpopulation.